Varietal performance and effect of planting method on yield and yield contributing characteristics of rice - Md. Mainul Hasan; Md. Amirul Alam; Mondal, M. Monjurul Alam; Puteh, Adam (Marsland Press, 2014)
The experiment was carried out to study the performance of two aman rice varieties (BRRI dhan31 and BRRI dhan41) under different planting methods (line sowing with sprouted seeds by drum seeder, haphazard transplanting and transplanting in line). Both the variety and planting method had significant effect on crop characters plant height, number of total tillers m-2, effective tillers m-2, grains panicle-1, sterile spikelets panicle-1, total spikelets panicle-1, grain yield except panicle length and 1000-grain weight. BRRI dhan41 produced the highest grain yield (4.06 t ha-1). Line sowing method with sprouted seeds by drum seeder showed better performance in respect of no. total tillers m-2 (415.81), effective tillers m-2 (401.85) and grain yield (4.80 t ha-1). The highest no. of total tillers m-2 (421.12), effective tillers m-2 (410.65) and grain yield (5.08 t ha-1) were recorded due to effect of the interaction of line sowing method with sprouted seeds by drum seeder and the variety BRRI dhan41.